Feelings of people waiting for an organ or tissue transplant in single queue - Melo, Givânya Bezerra de; Aguiar , Anne Karolyne Barros; Melo, Givanisy Bezerra de; Silva, Vívian Marcella dos Santos; Albuquerque, Maria Cícera dos Santos de; Brêda, Mércia Zeviani (Brazilian Journal of Transplantation, 2012)
Purpose: To identify the feelings of people who are waiting for an organ or tissue in a single transplantation list. Methods: This is a descriptive qualitative research conducted among seven people waiting for a transplant. Data were subjected to content analysis in the form of thematic or categorical analysis. Results: characterization of the subjects, 57% were female, ages between 22 and 62 years mean waiting for cornea, kidney and 2.1 years, 3.8 years. Five units of sense were identified in the beginning of the waiting: prevalence of negative feelings like sadness and uncertainty following the diagnosis and the need for transplantation; changes in life arouse negative feelings of worthlessness , guilt and passivity related to changes in the financial, leisure, freedom, life expectancy status, as well as positive feelings such as hope and overcoming by the appreciation for the family and life; in the confrontation, the family was the resource increasingly searched by the subjects, emerging positive feelings of trust and security; healthcare was taken along the waiting period by positive feelings to those waiting for a kidney and negative for those awaiting for a cornea by not attaing it; in such ambivalence it was disclosed positive feelings bringing the desire for the transplant, and causing negative feelings that keep life motivated by the death/life duality, compassion for the living donor; in the call for life , positive feelings of hope were disclosed before the awareness messages to encourage organ donation. Conclusion: Regardless the body, the wait for a transplant is a stressful time in the life of an individual, triggering multiple feelings which need to be assessed. Results address to foster the discussion on nursing education and practice about the importance of valuing the subjectivity of people waiting for a transplant, the need for health education during the waiting period, as well as improving the Organ and Tissue Harvesting System.